Hidden survival heterogeneity of three Common eider populations in response to climate fluctuations. (13th March 2017) - Guéry, Loreleï; Descamps, Sébastien; Pradel, Roger; Hanssen, Sveinn Are; Erikstad, Kjell Einar; Gabrielsen, Geir W.; Gilchrist, H. Grant; Bêty, Joël
Summary: Understanding how individuals and populations respond to fluctuations in climatic conditions is critical to explain and anticipate changes in ecological systems. Most such studies focus on climate impacts on single populations without considering inter‐ and intra‐population heterogeneity. However, comparing geographically dispersed populations limits the risk of faulty generalizations and helps to improve ecological and demographic models. We aimed to determine whether differences in migration tactics among and within populations would induce inter‐ or intra‐population heterogeneity in survival in relation to winter climate fluctuations. Our study species was the Common eider ( Somateria mollissima ), a marine duck with a circumpolar distribution, which is strongly affected by climatic conditions during several phases of its annual cycle. Capture‐mark‐recapture data were collected in two arctic (northern Canada and Svalbard) and one subarctic (northern Norway) population over a period of 18, 15, and 29 years respectively. These three populations have different migration tactics and experience different winter climatic conditions. Using multi‐event and mixture modelling, we assessed the association between adult female eider survival and winter conditions as measured by the North Atlantic Oscillation (NAO) index. We found that winter weather conditions affected the survival of female eiders from each of these three populations. However, different mechanisms seemed to be involved. Survival of the two migrating arctic populations was impacted directly by changes in the NAO, whereas the subarctic resident population was affected by the NAO with time lags of 2–3 years. Moreover, we found evidence for intra‐population heterogeneity in the survival response to the winter NAO in the Canadian eider population, where individuals migrate to distinct wintering areas. Our results illustrate how individuals and populations of the same species can vary in their responses to climate variation. We suspect that the found variation in the survival response of birds to winter conditions is partly explained by differences in migration tactic. Detecting and accounting for inter‐ and intra‐population heterogeneity will improve our predictions concerning the response of wildlife to global changes. Abstract : The authors used a reverse procedure based on capture‐recapture histories: using individual data in post‐hoc analyses could help to confirm heterogeneity in demographic parameters, a priori suspected, and identify its potential sources. The approach could be extended to other species and disciplines whenever heterogeneity is suspected but exhaustive individual data are missing.